SURROGATE MOTHER MENURUT HUKUM DI INDONESIA - Angga Pandu Wijaya, Nyoman; Novy Purwanto, I Wayan (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 01, Januari 2015)
This Paper is about Surrogate Mother by law in Indonesia. Problems occurred that Positive Law in Indonesia are not familiar with the terms of the Surrogate Mother. This paper aims to understand and know about Surrogate Mother by law in Indonesia. This writing, using the method of normative legal research with the type of analytical approach legislation (State approach). This paper presented a study that Indonesian law has no rules regarding the implementation of the engagement Surrogate Mother. Under the terms of the health law could not carry out a surrogate mother for clear rules of shrimp health legislation. Similarly, the rules in the realm of civil law, although Article 1338 of the Civil Code states that "All agreements made lawfully apply to the laws for those who make it" but Article 1320 of the Civil Code gives the terms validity of a treaty one of which is the cause of kosher. So that an agreement is made shall not be inconsistent with the rule of law. Surrogate Mother so that implementation can not be implemented.
Keywords: Surrogate Mother, Health Law, Civil Law